Autorzy:Jerzy Janowicz
Wydawnictwo:Nowa Era
Rok wydania:2016
Oblicz wartość wyrażenia 4.8 gwiazdek na podstawie 5 opinii

`a)\ 2^-3/2^-4+2^-5/2^-6+2^-7/2^-8+2^-9/2^-10=2^(-3-(-4))+2^(-5-(-6))+2^(-7-(-8))+2^(-9-(-10))=` 

`\ \ \ =2^(-3+4)+2^(-5+6)+2^(-7+8)+2^(-9+10)=2^1+2^1+2^1+2^1=8` 

 

`b)\ 3^6/3^-2-3^4/3^-1+3^-5/3^-8-3^-1/3^-9=3^(6-(-2))-3^(4-(-1))+3^(-5-(-8))-3^(-1-(-9))=` 

`\ \ \ =3^(6+2)-3^(4+1)+3^(-5+8)-3^(-1+9)=3^8-3^5+3^3-3^8=` 

`\ \ \ =-3^5+3^3=-243+27=-216` 

 

`c)\ 4^8/4^9+4^8/4^10+4^8/4^11=4^(8-9)+4^(8-10)+4^(8-11)=4^-1+4^-2+4^-3=` 

` \ \ \ =1/4+1/4^2+1/4^3=1/4+1/16+1/64=16/64+4/64+1/64=21/64`